A Ekonomi Gig atau Ketimpangan Digital? Pelajaran untuk Masa Depan Ketenagakerjaan Indonesia - Dwiputrianti, Septiana; Kotchegura, Alexander; Lee, Hye Kyoung (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
The gig economy has been widely celebrated for its potential to boost national productivity and generate flexible employment opportunities. Yet, beneath its promise lies the paradox of digital inequality. In Indonesia, the rapid growth of platform-based work in transportation, delivery, and online freelancing demonstrates the gig economy’s increasing visibility. However, compared to countries such as India, Brazil, and the United States, the measurable contribution of gig work to long-term economic resilience is less certain. Drawing on secondary data from the ILO, World Bank, and OECD, this paper argues that the gig economy, while expanding labour absorption, disproportionately depends on precarious, low-wage arrangements that limit upward mobility and sustainable growth. From a cultural perspective, gig work normalises hyper-flexibility and individualisation, reshaping the meaning of employment in ways that weaken collective bargaining and career stability. Comparative analysis reveals that countries with robust labour regulations have managed to harness gig productivity without exacerbating inequality, whereas emerging economies with weaker systems, such as Indonesia, risk deepening informalization. This study contends that Indonesia’s policy challenge is not whether the gig economy should grow, but whether it can grow inclusively. Without deliberate labour governance, Indonesia may face a dual economy: one sector benefiting from digital innovation, and another trapped in precarious, digitally mediated inequality.